Developing a coaching manual to provide human support for the Mothers and Babies Online (eMB) perinatal mental health intervention - Lara Baez; Jaime Hamil; Elaine McBride; Katherine A. Czech; Bayley J. Taple; Adriana Santillano; Mingjing Huang; Alinne Z. Barrera; S. Darius Tandon (Internet Interventions)
Background: Depression that occurs in pregnancy or postpartum (perinatal depression) impacts 1 in 5 mothers, yet access to effective and high-quality preventative interventions remains elusive for most. Digital interventions are a promising solution to this treatment gap because of the ubiquity of mobile devices and internet access. The Mothers and Babies Online Course (eMB) is an online adaptation of Mothers and Babies, an evidence-based preventative program for postpartum depression. Preliminary studies of eMB point to its potential efficacy, but low engagement with eMB was a major limitation. Leveraging home visitors as coaches to guide clients through eMB may be a way to increase uptake and engagement, and ultimately improve outcomes when implemented in home visiting programs. Objective: The aim of this study was to implement user-centered design methods to develop a coaching manual for home visitors to implement eMB. Methods: 10 parents and 10 home visitors were interviewed individually. Measures included a “think aloud” activity and a semi-structured interview focused on gaining insight into parent and home visitor needs and preferences regarding eMB coaching in the context of home visiting. Thematic analysis was used to derive themes and sub-themes from interview transcripts. Results: Parents were enthusiastic about eMB, but noted barriers including limited time and forgetfulness. Parents also thought that their home visitor would be the ideal eMB coach because of the existing close relationship. Home visitors shared that eMB would fit seamlessly into their home visiting workflow. They also thought that home visitors could address challenges that parents encounter in using eMB and leverage their relationship with parents to crystalize learning. Home visitors also noted that a coaching manual would be a key part of successful eMB implementation. Thus, valuable insights from parents and home visitors were used to create a coaching manual. Conclusions: Parents and home visitors were both enthusiastic about eMB with adjunctive coaching, and home visitors agreed that a coaching manual would be vital in guiding them to help parents through eMB. Results highlight the importance of engaging end-users in all aspects of online intervention design, including the coaching manual. The effectiveness of the intervention and utility of the coaching protocol will be evaluated in a future pilot trial.